Class dynamics and the configuration of democracy: The case of entrepreneurs - Domènech Sampere, Xavier (Hispania Nova, 2024)
This article highlights the role of businessmen in their ability to steer and determine crucial aspects of Spanish political change in the 1970s. In contrast to the interpretation that Spanish businessmen were a sort of “impotent privileged” class under Francoism and, consequently, incapable of influencing the process of democratizing political change, this text analyzes how businessmen experienced an extraordinary accumulation of organizational resources, and their own unification as a class, under Francoism. In this framework, the strong crisis of legitimacy and hegemony that they will experience at the beginning of the process of political change can be faced with a strong mobilization of resources and the creation of a new employers’ organization in an extraordinarily short time, capable of transforming their relationship with political power at the end of the period of creation of a new political regime.
Keywords: Francoism; transition; democracy; businessmen; class struggle